Nuances da dominação do conhecimento em gestão: caso de programa de mestrado internacional no Brasil - Teixeira, Ana Christina Celano (2014)
The purpose of this study is to understand how the practice of an international management education program reveals the dominance of knowledge in the moment of its internationalization to emerging countries. The scenario used takes into account changes in the contemporary international context, particularly in terms of the inclusion of emerging countries such as India, China and Brazil among the academic partners of education programs in management. More specifically, the contribution of the article results from the critical approach focused on management education that recognizes the role of emerging countries in the production and consumption of knowledge. The questioning of the subject, following a qualitative approach, is based on the description and analysis of the IMPM (International Masters in Management Practice) with recent academic partnerships in China and in Brazil. The results indicates that international education programs in management are interested in performing activities in emerging countries, but these partnerships not always result in a legitimate role that move them from their peripheral positions to the center of knowledge production in management. Finally, we raise the question that international education programs in management, though present in these countries through the establishment of local modules or the participation of students of these countries continue to function as instruments to disseminate universal management knowledge.